Fast nondiffusive response of heat and turbulence pulse propagation - Naoki Kenmochi; Katsumi Ida; Tokihiko Tokuzawa; Yoshinori Mizuno; Ryo Yasuhara; Hisamichi Funaba; Hiyori Uehara; Daniel J. Den Hartog; Mikirou Yoshinuma; Yuki Takemura; Hiroe Igami; Ryoma Yanai (Scientific Reports, 2024)
Abstract The experimental findings from the Large Helical Device have demonstrated a fast, nondiffusive behavior during the propagation of heat pulses, with an observed increase in speed with reduction in their temporal width. Concurrent propagation of the temperature gradient and turbulence, in a timeframe spanning from a few milliseconds to tens of milliseconds, aligned with the avalanche model. These results indicate that the more spatiotemporally localized the heat and turbulence pulses are, the greater the deviation of the plasma from its equilibrium state, coupled with faster propagation velocity. This insight is pivotal for future fusion reactors, which necessitate the maintenance of a steady-state, non-equilibrium condition.